2012
DOI: 10.4049/jimmunol.1103264
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Laser Burn-Induced Neuropathy Leads to Substance P-Dependent Loss of Ocular Immune Privilege

Abstract: Inflammation in the eye is tightly regulated by multiple mechanisms that together contribute to ocular immune privilege. Many studies have shown that it is very difficult to abrogate the immune privileged mechanism called anterior chamber associated immune deviation (ACAID). Previously, we showed that retinal laser burn (RLB) to one eye abrogated immune privilege (ACAID) bilaterally for an extended period of time. In an effort to explain the inflammation in the non-burned eye, we postulated that neuronal signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 37 publications
3
34
0
Order By: Relevance
“…11 Interestingly, laser burns to the retina induce an upregulation in NK1-R, the receptor for SP, which is associated with the abrogation of ACAID. 26,27 Accordingly, we examined the eyes of mice following trephining for the upregulation NK1-R message in trephined eyes and the contralateral nonmanipulated eyes of BALB/c mice. The results revealed a spike in NK1-R message 14 days following trephining and a return to baseline levels by day 21 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…11 Interestingly, laser burns to the retina induce an upregulation in NK1-R, the receptor for SP, which is associated with the abrogation of ACAID. 26,27 Accordingly, we examined the eyes of mice following trephining for the upregulation NK1-R message in trephined eyes and the contralateral nonmanipulated eyes of BALB/c mice. The results revealed a spike in NK1-R message 14 days following trephining and a return to baseline levels by day 21 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…28 Similarly, laser burns to the retina elicit a 10-fold increase in the expression of NK1-R in the opposite eye and prevent the induction of ACAID in both eyes. 26 With this in mind, we examined the effect of trephining, SP, and orthotopic corneal transplantation on the induction of ACAID in both eyes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been postulated that ACAID is difficult to abrogate; however, it has been recently reported that unilateral injury to one eye such as retinal laser burn (Qiao et al, 2009), ON crush or trauma in different regions of the optic pathway (Stein-Streilein, 2012), abrogate ACAID bilaterally for an extended time period. Lucas et al (2012) suggested that the substance P (an inflammatory neuropeptide) acts in the neurologic communication between the two eyes and is involved in the loss of immune regulation post-ocular trauma. It is now well accepted that neurogenic mechanisms contribute to the symmetrical spread of inflammation in rheumatoid arthritis (Donaldson et al, 1995;Kelly et al, 2007) and that transneuronal signaling between damaged neurons and their contralateral homologues prevent the spread of peripheral nerve damage (Kolston et al, 1991).…”
Section: Mechanisms Responsible For Contralateral Eye Involvementmentioning
confidence: 99%
“…Amacrine-derived SP has been reported to be involved in the loss of immune privilege post retinal laser burn through its potential to promote an inflammatory environment that in turn activates resident macrophages and microglia. NK1R antagonists could prevent or curb inflammation post ocular trauma (Lucas et al, 2012). On the other hand, there are reports on anti-inflammatory effects of SP in the retina.…”
Section: Immunomodulatory Role Of the Substance P In Diseasementioning
confidence: 99%